FORECASTING THE NUMBER OF UNEMPLOYED IN THE LABOR MARKET OF THE REPUBLIC OF UZBEKISTAN USING TREND MODELS - Hojiqulova Feruza Dona qizi; Kenjayeva Saboxat Safarovna (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
We know that a number of measures are being implemented in our country to find a solution to the labor problem, and theoretically, its economic analysis is considered a very important factor for our national economy. Because at present, finding a solution to the employment problem, reducing the weight of a number of countries, as well as in our country, increasing the number of jobs that are created based on the demand and supply of our time, represents the future state of this market and our general economy. This article talks about the Arima model of forecasting and analyzes the unemployment rate using this model.